Program complex for research temperature segregation in asphalt concrete mixes - Leonovich, Ivan I.; Kovalchuk, Alexander S.; Pumpur, Vladimir A. (Technological and Economic Development of Economy, 2005)
The problem of temperature segregation which is the reason of the damage of asphalt concrete coverings of highways is described in the article. The description of a mathematical model of the process of heat exchange during transportation is given. The interface of software is described. Preliminary results of the numerical decision of the problem of heat exchange are described.Article in Russian.Programinis kompleksas temperaūros segregacijai asfaltbetonio mišinyje tirtiSantrauka. Straipsnyje aprašomas asfaltbetonio mišinio temperatūros segregacijos tyrimo matematinis modelis ir programinis kompleksas, kai jis automobilio kėbule pervežamas iš gamyklos į naudojimo vietą. Pateiktas darbo su programine įranga aprašymas. Apibūdintos programos galimybės ir pateikti preliminarūs skaičiavimo rezultatai.Reikšminiai žodžiai: asfaltbetonio mišinys, temperatūros segregacija, šilumos nuostoliai.Программный комплекс для исследования температурной сегрегации в асфальтобетонной смесиРезюме. Описана математическая модель и программный комплекс для исследования температурной сегрегации в асфальтобетонной смеси, которая транспортируется в кузове автомобиля с завода на участок дороги. Дано описание интерфейса программного обеспечения. Описаны предварительные результаты и возможности программного комплекса.Ключевые слова: асфальтобетонная смесь, температурная сегрегация, тепловые потери.First Published Online: 21 Oct 2010